Computer Fundamentals and Programming in C - Dey, Pradip (Oxford University Press, 2006)
Computer Fundamentals and Programming in C is designed to serve as a textbook for students of undergraduate computer engineering, MCA and BCA for the introductory course on computers and programming. The book begins with an introduction to the number systems, binary arithmetic, logic gates and basic concepts of operating systems. The rest of the book provides an exhaustive coverage of programming in C for the reader to acquire skills of writing programs in C. Some advanced features of C have also been included. The book also includes a comprehensive case study on simulation of OS system calls using C language. Interspersed with numerous solved examples based on daily life, the theory is also well supported by plenty of review questions and programming exercises at the end of each chapter. Written in a clear and lucid style, the book encourages self-study and motivates the student towards independent problem solving